The Impact of using Rice Husks Ash, Seawater and Sea Sand on Corrosion of Reinforcing Bars in Concrete - Patah, Dahlia; Dasar, Amry (Journal of the Civil Engineering Forum, 2023)
The global increase in infrastructure development has led to potential shortages of river sand and tap water, particularly in coastal areas, posing challenges for concrete production. To address this issue, numerous studies have been conducted on the use of seawater and sea sand as sustainable alternatives. Rice Husks Ash (RHA), a fine powder derived from the combustion process of agricultural husks, has emerged as potential eco-friendly solution due to its excellent pozzolanic properties, making it a viable candidate for partially replacing cement in concrete. This substitution enhances concrete durability and strength as well as reduces the risk of corrosion in harsh environmental conditions. Therefore, this study examined impact of seawater for mixing, sea sand and substitution ratio of RHA on corrosion of reinforcing bars. The specimen used in the experiment had a thickness of 150 mm, with rectangular areas of 400 x 400 mm and plain steel bars with a diameter of 10 mm. Corrosion levels and concrete quality were evaluated using the half-cell potential (HCP) method and hammer test, respectively. The results showed that all specimens mixed with seawater, river sand, and different substitution ratios of RHA (0%, 5%, 10%, and 15%) exhibited corrosion, as confirmed by the HCP method. However, only the specimen mixed with tap water, sea sand, and an addition of 5% RHA demonstrated effective resistance to corrosion, comparable to normal concrete.